PENGARUH PERBEDAAN LABA AKUNTANSI DAN LABA FISKAL SERTA ROA TERHADAP CUMULATIVE ABNORMAL RETURN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2009 - Indra Pahala; Tresno Eka Jaya; Grace Ombun Meilisa (Jurnal Ilmiah Econosains, 2012)
ABSTRACTIn general, investor inculcates ithe capital into company through stock market to obtain earnings from ithe investment rate of return. On the other side, company requires fund to going concern and to do activity from investor. Therefore, company requires trust from investor through appraisal of performance coming from ROA. In reporting of income often happened difference between accounting incomes and fiscal income. This research aim to know difference influence between accountingincomes and fiscal income and Return On Assets (ROA) to Cumulative Abnormal Return (CAR) at inscribed manufacturing business in BEI in the year 2009. This research variable is difference of accounting income and fiscal income (X1), ROA (X2) and CAR (Y). Sample total 77 companies. Data applied is financial statements and the price of stock from each company sample obtained in BEI. Analytical method applied is in this research is quantitative method with testing of classic assumption and doubled linear regression analysis. While testing of hypothesis done with determination analysis (R2), significance test simultan (test F) and individual parameter significance test (test t) with Î± = 5%. Test Result F indicates that difference variable between accounting incomes and fiscal income and ROA has influence signifikan simultan to CAR. This thing is visible from output SPSS showing level of signifikansi which less than Î± (0.021 < 0.05). While test result t this research indicates that difference between accounting incomes and fiscal income influential positive to CAR posed at with level of signifikansi which less than Î± (0010 < 005). Result of this research in line with research of Lev and Nissim (2004) that book-tax differences influential positive to return stock. In this research ROA doesn't have an effect on to CAR posed at with level of signifikansi which more than Î± (0221 < 005). This research in line with research of Sasongko and Wulandari (2005), Mukhtaruddin and Romalo (2007) and Stella (2009) in their research concluding that return on assets doesn't have an effect on to the price of stock. Key words: Book-Tax Differences (BTD), Return On Assets (ROA), Cumulative Abnormal Return (CAR)